EFFECT OF CYSTEAMINE SUPPLEMENTATION IN SEMI DEFINED MEDIA ON IN VITRO PRODUCTION OF BUFFALO EMBRYOS - PALANISAMY, A; RANGASAMY, S; SATHESHKUMAR, S; KUMANAN, K (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to investigate the effect of cysteamine supplementation in semi defined media like synthetic oviductal fluid (SOF) media during various stages of in vitro culture on buffalo preimplantation embryo development. Six independent trials with a total of one hundred andseventy four oocytes were carried out with cysteamine supplementation at 1 00μM/ml during in vitro maturation (IVM), fertilization (IVF) and culture (IVG), one hundred twenty six oocytes without supplementation served as control. The mean cleavage rates were 24.1 ±1.67and 19.8±0.89 per cent inthe treatment and control group, respectively. The percentage of morula that developed in treatment andcontrol group were 15.1 ±1.35 and 7.9±1.47, respectively. The percentage of embryo that developed tothe morula stage were significantly higher (P
Keywords: Buffalo; Cysteamine; In vitro fertilization; Embryo